Ethylmalonic acid modulates Na+, K+‐ATPase activity and mRNA levels in rat cerebral cortex. Issue 3 (6th December 2012) - Schuck, Patrícia Fernanda; De Assis, Dênis Reis; Viegas, Carolina Maso; Brandão Pereira, Talita Carneiro; Machado, Jéssica Luca; Furlanetto, Camila Brulezi; Bogo, Mauricio Reis; Streck, Emilio Luiz; Ferreira, Gustavo Costa
Abstract Ethylmalonic acid (EMA) accumulates in tissues of patients affected by short‐chain acyl‐CoA dehydrogenase deficiency and ethylmalonic encephalopathy, illnesses characterized by variable neurological symptoms. In this work, we investigated the in vitro and in vivo EMA effects on Na+, K+‐ATPase (NAK) activity and mRNA levels in cerebral cortex from 30‐day‐old rats. For in vitro studies, cerebral cortex homogenates were incubated in the presence of EMA at 0.5, 1, or 2.5 mM concentrations for 1 h. For in vivo experiments, animals received three subcutaneous EMA injections (6 μmol g−1; 90‐min interval) and were killed 60 min after the last injection. After that, NAK activity and its mRNA expression were measured. We observed that EMA did not affect this enzyme activity in vitro. In contrast, EMA administration significantly increased NAK activity and decreased mRNA NAK expression as assessed by semiquantitative reverse transcriptase polymerase chain reaction when compared with control group. Considering the high score of residues prone to phosphorylation on NAK, this profile can be associated with a possible regulation by specific phosphorylation sites of the enzyme. Altogether, the present results suggest that NAK alterations may be involved in the pathophysiology of brain damage found in patients in which EMA accumulates. Synapse, 2013. © 2012 Wiley Periodicals, Inc.